A Proof of Principle Study of the Terminal Sterilization of Prefilled Syringes Using A Water Cascade Process - Drost-Wijnne Anne J.A; Van Wezel Ralph A.C; Deenen Maarten J.; Van Doornmalen Gomez Hoyos Joost P.C.M; Grouls René J.E (De Gruyter, 2018)
A new development in drug compounding is the production of ready-to-administer sterilized prefilled syringes. A challenge with these syringes is the method of terminal sterilization. There is no information available whether water cascade sterilization is a suitable method. We investigated the effect of this sterilization method on cyclic olefin (co)polymer (CCP/COC) syringes.